Revitalisasi Pendidikan Bahasa Arab Berbasis Pendidikan Life Skill Pada Jurusan Pendidikan Bahasa Arab Di Iain Tulungagung Dalam Menghadapi Masyarakat Ekonomi Asean (MEA) - Adi Marsono (Jurnal Dinamika Ekonomi Syariah, 2020)
The background of this research is that the emergence of the revitalization of education become the talk very interesting and crucial entered the times of the ASEAN Economic Community (MEA) recently. Seeing the condition of a nation that increasingly worse with a variety of educational failure phenomena occurring generation of people. At the regional level (ASEAN), Arabic is the language of the second alternative communication after the Malay language. Since Arabic is the language of the religious culture of the Islamic community of Malay and Arabic language turns more dominant than in English. This is because the majority of the people of ASEAN are Muslims who think that the Arabic language is flexible, open and elastic in answering the challenges of globalization and cultural transformation. State Islamic Institute (IAIN) Tulungagung is one of the universities which have policies, matakuliah, environment and curriculum that supports the education of Arabic-based life skill education in the ASEAN Economic Community mengahadapi (MEA). The method used in this research are : the type of research is qualitative descriptive. Methods of data collection are observation, interview, documentation. Methods of data analysis are reduction, data display and then drawing conclusions / verification.The results of this research are : 1) the revitalization of the Arabic language education based life skills education at State Islamic Institute (IAIN) Tulungagung in the ASEAN Economic Community (MEA) is conducted by: a) To formulate vision and mission that suppor Competence Life Skills Arabic, b) Develop curriculum a greater emphasis on deepening the Arabic language skills competence, c) Establishing Bi'ah Lughawiyah Arabic language in Campus and Ma'had, d) Create a special program of learning the Arabic language, e) Mastery learning strategies and Arabic language skills, f) Lecturer Professional and have optimum competence, g) Provide additional extra-based Life Skills, and h) To sharpen the practical and Delivers Native speakers. 2) The implications of life skill education to the Arabic language education at State Islamic Institute (IAIN) Tulungagung for facing the ASEAN Economic Community, the following: a) Linking the use of language in context, b) Lecturer more frequent use of the media, c) Institutions must make improvements in particular, d) Optimization Arabic Education management, and e) Overcoming the obstacles faced.